Treatment of rabies in the 21st century: curing the incurable?. (October 2011) - Franka, Richard; Rupprecht, Charles E
Despite the extreme case fatality attributable to rabies, reports of survivors provide a faint glimpse of a possibility of overcoming this deadly disease, even after clinical symptoms manifest. At present, no existing approach fulfills modern medical criteria for the optimal therapy of rabies. Until new efficacious antiviral compounds and optimized treatment protocols are developed, animal population management and vaccination of major reservoirs and vectors, minimization of the risk of viral exposures, and appropriate and early postexposure prophylaxis, remain the hallmarks of modern public health intervention.